Coumarin–carbazole based functionalized pyrazolines: synthesis, characterization, anticancer investigation and molecular docking. Issue 44 (13th August 2021) - Patel, Mrugesh; Pandey, Nilesh; Timaniya, Jignesh; Parikh, Paranjay; Chauhan, Alex; Jain, Neeraj; Patel, Kaushal
Abstract : Coumarin–carbazole based functionalised pyrazolines: synthesis, anticancer activity and molecular docking. Abstract : A series of novel pyrazoline scaffolds from coumarin–carbazole chalcones were synthesized. We explored various acetyl, amide, and phenyl substituents at the N -1 position of the pyrazoline core. The synthesized compounds were characterized by FTIR, 1 H-NMR, 13 C-NMR, DEPT, and mass spectroscopic techniques. The in vitro cytotoxicity study of all the synthesized compounds was evaluated against HeLa, NCI-H520 and NRK-52E cell lines. Compounds 4a and 7b became the most active compounds and exhibited their potential to arrest the cell cycle progression and induce apoptosis in both the cell lines. In addition, molecular docking studies revealed a higher binding affinity of both the molecules with CDK2 protein. Based on the obtained results, a comprehensive analysis is warranted to establish the role of compounds 4a and 7b as promising cancer therapeutic agents.